N921 - PARKER,P (Tufts Archival Research Center, 2007)
Chapter column on New York State's Indoor Air Quality Day. Describes resolution that indoor air quality (IAQ) is a serious issue and that IAQ day should be used to educate the public and officals on the importance of IAQ. Plans on demonstrations by construction sites.